A Prospective Study on Blood Culture Positivity and Antimicrobial Resistance in Neonatal Sepsis in a Tertiary Care Hospital - Ashraf, Faria; Ali, Ahmad (Journal of Neonatal Surgery, 2025)
Background: Neonatal sepsis remains a leading cause of morbidity and mortality in developing countries. Early identification of pathogens and their antibiotic susceptibility patterns is essential for optimal therapy. Objectives: To determine the rate of blood culture positivity, bacterial spectrum, and antibiotic resistance patterns among neonates with clinically suspected sepsis. Methods: A prospective observational study was conducted over 12 months in the Neonatal Intensive Care Unit (NICU) and Microbiology Department at VIMS Medical College, Gajraula. A total of 200 neonates with clinical suspicion of sepsis were enrolled. Blood samples were collected aseptically and cultured using BACTEC automated system. Isolates were identified by standard biochemical tests, and antimicrobial susceptibility testing was performed using the Kirby–Bauer disc diffusion method as per CLSI (2023) guidelines. Results: Of the 200 samples, 88 (44%) showed positive blood culture results. Gram-negative bacteria predominated (65.9%), with Klebsiella pneumoniae (27.3%) and Escherichia coli (22.7%) being the most frequent isolates, followed by Staphylococcus aureus (20.4%) and Coagulase-negative Staphylococci (15.9%). Gram-negative isolates showed high resistance to ampicillin (89%) and third-generation cephalosporins (68%), but retained sensitivity to meropenem (78%) and amikacin (72%). Among S. aureus isolates, 36% were methicillin-resistant (MRSA). Conclusion: Gram-negative bacteria, particularly K. pneumoniae and E. coli, remain the predominant pathogens in neonatal sepsis with alarming resistance to commonly used antibiotics. Regular surveillance and antibiotic stewardship are crucial to improve neonatal outcomes